Is Mitochondrial Uncoupler Dinitrophenol Effective in Counterbalancing the Dilution Effect in Buffalo Semen? - Arjun, Venkateshappa; Kumar, Pradeep; Dutt, Ravi; Kumar, Dharmendra; Kumar, Amit; Bala, Renu; Verma, Nisha; Jerome, Andonissamy; Virmani, Meenakshi; Patil, Chandrashekhar; Bhardwaj, Shivani; Yadav, Prem Singh (The Indian Journal of Animal Reproduction, 2022)
Semen ejaculates were collected from Murrah buffalo (Bubalus bubalis) bulls and were diluted with low density lipoprotein (LDL) based extender into 20 million sperm/0.25 mL and 2 million sperm/0.25 mL. Dinitrophenol (DNP) was added (@ 0, 1, 10 and 50 µM) to 20 million and 2 million sperm concentration cryopreserved. After thawing, the parameters studied were plasma membrane integrity by HOST, sperm motility and kinetics by CASA, the thermal resistance of sperm by incubation test, mitochondrial superoxide status by MitoSOX through flow cytometry, mitochondrial membrane potential (MMP) evaluation by JC-1 through flow cytometry. There was no significant (P>0.05) change in plasma membrane integrity, sperm motility and kinematics; thermal resistance of sperm, mitochondrial superoxide status and hMMP in comparison to control within the 2 and 20 million sperm doses. Two million sperm doses resulted in low plasma membrane integrity, low thermal resistance of sperm, high mitochondrial superoxide status and decreased high MeMP and no significant (P>0.05) change in sperm motility and kinematics, but reduced total motility, beat cross frequency and no change in progressive motility, straight linear velocity, average path velocity, curvilinear velocity, the amplitude of lateral head displacement, straightness, linearity, and wobble in comparison to 20 million sperm doses. Supplementation of DNP (0, 1, 10 and 50 μM) in extender failed to improve semen quality in both 2 and 20 million sperm doses in buffalo.